2016
DOI: 10.1021/acs.nanolett.5b04814
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Polar Fluctuation and Lattice Mismatch on Carrier Mobility at Oxide Interfaces

Abstract: Since the discovery of two-dimensional electron gas (2DEG) at the oxide interface of LaAlOinterface. The minimal thickness of the polar layer t C that is required for electronic reconstruction is t C =  0  P E/eP, where  P is the dielectric constant of the polar material, E is the energy gap separating the valance band of the polar layer and the conduction band of the nonpolar material, and P is the electric polarization of polar layers [10]. Taking  P = 24, E as STO bandgap of 3.2 eV, and P = 0.526 C m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
73
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 43 publications
2
73
0
Order By: Relevance
“…30 Here we report studies of the MR of LSAT deposited epitaxially on (111) STO. LSAT has a 1% lattice mismatch with STO, as opposed to a 3% mismatch in the case of LAO/STO, 31 which leads to a comparatively lower strain. As with the (001) LAO/STO heterostructures, we find that the SOI can be tuned by V g .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…30 Here we report studies of the MR of LSAT deposited epitaxially on (111) STO. LSAT has a 1% lattice mismatch with STO, as opposed to a 3% mismatch in the case of LAO/STO, 31 which leads to a comparatively lower strain. As with the (001) LAO/STO heterostructures, we find that the SOI can be tuned by V g .…”
mentioning
confidence: 99%
“…The sample had 12 monolayers of LSAT deposited on (111) oriented STO using pulsed laser deposition, at a growth partial oxygen pressure of 10 −4 Torr. 31,32 No post growth annealing step was performed. Ti/Au was deposited on contact pads of the Hall bars, and Al wirebonds were made to allow for a 4-probe measurement of transverse and longitudinal resistance.…”
mentioning
confidence: 99%
“…Earlier work on (001) LAO/STO interfaces 15 demonstrated that strain at the interface can drastically change conduction, whereas recent studies of LSAT grown on (001) STO suggested that the lower strain compared to LAO significantly increased the carrier mobility. 24,29 However, there have been only a few transport experiments performed on LSAT/STO interfaces to date, and none on (111) oriented LSAT/STO. In particular, the effect of an electric field, which has proved to be a powerful tool to probe the properties of other STO based interface devices, has not been studied in the case of LSAT/STO.…”
mentioning
confidence: 99%
“…Actually, a small lattice mismatch between the film and the substrate is expected to improve the crystalline quality of the heterointerface, thus increases the scattering time and accordingly electron mobility, which is extremely difficult to accurately quantify from first‐principles calculations, though. For example, very recently, Ariando and co‐workers have reported that by replacing LaAlO 3 with cubic (La 0.3 Sr 0.7 )(Al 0.65 Ta 0.35 )O 3 (LSAT), the lattice mismatch between the film and the SrTiO 3 substrate is reduced from 3.0% to 1.0%, and interfacial electron mobility can be significantly improved (about 35 000 cm 2 V −1 s −1 at 2 K), which is almost 30 times larger than that in the conventional LaAlO 3 /SrTiO 3 . One the other hand, Gunkel et al proposed that the reduced epitaxial strain in LSAT/SrTiO 3 has only minor effects on the improved mobility.…”
Section: Introductionmentioning
confidence: 99%